Tingkat Ketuaan Bahan Setek dan Konsentrasi IAA pada Pertumbuhan Setek Lada - Sugiatno, Sugiatno; Nurmauli, Niar; Susanto, Herry (Universitas Lampung, 2024)
Pepper plant propagation generally uses stem cuttings. Choosing the maturity level of the cutting will determine the subsequent growth of the cutting, because the body parts of the plant contain different food reserves and endogenous auxin. The growth regulator Indole Acetic Acid is used to stimulate the growth of roots and shoots of cuttings. The research aims to determine the effect of the level of maturity of the cutting material and IAA concentration on the growth of pepper seedlings and to determine the effect of the interaction between the two treatments. Research was carried out in the Greenhouse and Plant Science Laboratory, Faculty of Agriculture, University of Lampung. The experimental design used a completely randomized design (RTS), homogeneity was tested with the Bartlett test, non-additivity was tested with the Tukey test. Analysis of variance and least significant difference test (LSL) were carried out at the 5% level. The research results concluded (1). Cuttings originating from the middle part grew faster, namely in sprouting shoots, length of cutting shoots, number of leaves, and dry weight, but there was no significant difference in the dry weight of cutting roots. (2). An IAA concentration of 500 ppm gave the best response to shoot sprouting, shoot length of cuttings, number of leaves, and root dry weight. (3). Cuttings originating from the middle section that were applied with IAA 500 ppm were the best combination in terms of shoot emergence, shoot length, number of leaves, and shoot dry weight. Key words: cuttings, indole acetic acid, black pepper